KONFERENSI JOGJA 1955: SUATU MOMENTUM MENUJU KEBANGKITAN MILITER PRETORIAN DI INDONESIA - Noor, Ph.D, Firman (Indonesia Defense University, 2013)
Today, Indonesia has enjoyed a limited role of military in politics. But not long time ago, during the New Order Era, the role of military was strong and even omnipresents. This paper wants to trace back the moment that indicates the early stage of the Indonesia military to be independent power, which was also implying the very characteristic of praetorian. From the discussion, we can see that the TNI outlook as one of the powerful body in Indonesia political system evolves gradually. The position of military was in fact at a nadir point when the civilian politicians took control in every aspect of national politics, particularly in the early years of â€œLiberal Democracyâ€ era. The Jogja conference in 1955 indicates the important shift from professional to be praetorian in Indonesia military history.Â Keywords : praetorian, civil supremacy, military politics,TNI